Prevalence and Factors Associated with Anxiety among School Students - Neupane, Nira; Pradhan Thaiba, Anupama; Singh, Archana; Shrestha, Pragya; K C, Reshma (Academia Research Journal, 2024)
Anxiety is a feeling of uneasiness or distress that results from negatively interpreting a situation. It is necessary to explore the extent and related factors of anxiety in students as it is one of the most prevalent childhood disorders. When a student is anxious, their working memory is affected and they are unable to learn. The cross-sectional descriptive study was conducted to assess the prevalence and associated factors with anxiety among school students at Kashi Noble Academy in Siddharthanagar Municipality -12, Bhairahawa, Rupandehi. Non-probability purposive sampling was used to collect data from 187 students. The data was collected using a structured self-administered questionnaire and the Modified Hamilton Anxiety Rating Scale. The data were analyzed using descriptive and inferential statistics; mainly frequency, percentage, mean, and chi-square. The findings of the study showed that out of 187 students, 52.4% were male and 47.6% female, 76.5% had mild anxiety, 18.7% had mild to moderate anxiety and 4.8 % had moderate to severe anxiety. There was a significant association between the prevalence of anxiety and age (p=0.033), sex (x2=10.41, df= 2, p=0.006), and type of family (x2=4.94, df= 1, p=0.026). Based on the findings of the study, anxiety is more common among female students, students living with nuclear families, and students who are under a lot of academic pressure. The study advised making the required lifestyle changes, however, the gender of the participants could not be changed. As a result, to become mentally healthy, kids should adopt healthy lifestyle patterns (enough rest, sleep, and exercise), and schools should engage in anxiety prevention programs and encourage students to participate in extracurricular activities.